Livestock and food production in Africa: Challenge and opportunity for the national livestock and veterinary services - Anteneh, A. (1989)
Describes trends and difficulties in livestock production and consumption in Africa, and the economic objectives that play an important role in African husbandry. Examines the role of livestock and veterinary services in Africa. Discusses constraints and opportunities. Looks into the role of regional and international organisations such as IBAR, ECA, ILRAD and ILCA.